2018
DOI: 10.1080/2162402x.2017.1423167
|View full text |Cite
|
Sign up to set email alerts
|

CD44v6 as innovative sarcoma target for CAR-redirected CIK cells

Abstract: Purpose of our study was to explore a new immunotherapy for high grade soft tissue sarcomas (STS) based on cytokine-induced killer cells (CIK) redirected with a chimeric antigen receptor (CAR) against the tumor-promoting antigen CD44v6. We aimed at generating bipotential killers, combining the CAR specificity with the intrinsic tumor-killing ability of CIK cells (CAR+.CIK). We set a patient-derived experimental platform. CAR+.CIK were generated by transduction of CIK precursors with a lentiviral vector encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…We and others studied the use of CAR expressing CIK in STS (32)(33)(34)(35). In our previous study, we demonstrated the preclinical effectiveness of CAR-redirected CIK against CD44v6, which is expressed in about 40% of STS (32).…”
Section: Introductionmentioning
confidence: 98%
“…We and others studied the use of CAR expressing CIK in STS (32)(33)(34)(35). In our previous study, we demonstrated the preclinical effectiveness of CAR-redirected CIK against CD44v6, which is expressed in about 40% of STS (32).…”
Section: Introductionmentioning
confidence: 98%
“…In mice models, was found an inverse correlation of recovery of NKT cells and GVHD after alloHSCT while preserving a graft-versus-tumor response (200). NKT cells can also be expanded in vitro and can be genetically modified to express CAR (201,202). Thanks to limited TCR alloreactivity and emerging technology to obtain large numbers, NKT cells represent another attractive source to generate off-the-shelf CAR+ immune cells.…”
Section: Alternative Off-the-shelf Car Carriersmentioning
confidence: 97%
“…The in vivo antitumor activity of CD44v6-CAR-CIK cells is also present in subcutaneous xenografts. Significant greater delay of tumor growth in CD44v6-CAR-CIK cell-treated mice was seen compared to untreated and control-treated mice [67]. For these reasons, CD44v6 may be a favorable target for CAR-T cells in future sarcoma clinical trials.…”
Section: Cd44v6mentioning
confidence: 98%
“…Recently, CD44v6 was a therapeutic target for CAR-redirected cytokine-induced killer (CIK) T cells for soft tissue sarcoma patients [67]. CD44v6 had an expression average of 40% amongst soft tissue sarcomas such as liposarcoma, fibrosarcoma, leiomyosarcoma, and undifferentiated pleomorphic sarcoma.…”
Section: Cd44v6mentioning
confidence: 99%